Endogenous Product Differentiation in Credit Markets: What Do Borrowers Pay For? - Moshe Kim; Eirik Gaard Kristiansen; Bent Vale (Norges Bank, 2004)
This paper studies strategies pursued by banks in order to differentiate their services and soften competition. More specifically we analyse whether bank's ability to avoid losses, its capital ratio, or bank size can be used as strategic variables to make banks different and increase the interest rates banks can charge their borrowers in equilibrium. Using a panel of data covering Norwegian banks between 1993 and 1998 we find empirical support that the ability to avoid losses, measured by the ratio of loss provisions, may act as such a strategic variable. A likely interpretation is that borrowers use high-quality low-loss banks to signal their creditworthiness to other stakeholders. This supports the hypothesis that high-quality banks serve as certifiers for their borrowers. Furthermore, this suggest that not only lenders and supervisors but also borrowers may discipline banks to avoid losses.
hdl:11250/2498715
Keywords: G21; L15; 330; banking; product differentiation; certification; market discipline